Pengukuran Utilitas Dana Kapitasi Puskesmas Dengan Capaian Standar Pelayanan Minimal Kesehatan di Indonesia - Imam Sumardjoko; Muhammad Heru Akhmadi (Universitas Gorontalo, 2020)
Abstract The JKN program is a big step towards creating wider access to health services to the community. This program has covered around 60 percent of the total population of Indonesia. Public-Health Center (Puskesmas) is the largest entry-level health facilities that receives capitation funds for 8.53 trillion rupiah in 2017. Utilization of capitation funds varies from each Puskesmas. Payment of capitation funds has an increasing trend in line with the number of BPJS Health membership which is increasing towards universal health coverage. This study explores the utilization of Puskesmas capitation funds and health minimum service standard achievements. The research data covers the Puskesams in Cirebon City during the period 20172018. The variables that measure are SiLPA capitation funds, and minimum health service standards. Hypothesis formulation states there are differences in the achievement of minimum health service standards in the health sector in entry-level health facilities which have a low capitation SiLPA fund and a puskesmas that has a high SiLPA value. The Lilliefors test calculation results for the research sample yielded an L value of 0,1725 with normally distributed data. Homogeneity testing showed a homogeneous variant value with an F hit of 0,297. The results shows that there was no variance in the achievement of minimum health service standards of Public-Health Center in Cirebon CityAbstrak Program JKN menjadi langkah besar untuk menciptakan akses layanan kesehatan yang lebih luas kepada masyarakat. Program ini telah mencakup sekitar 60 persen dari total penduduk Indonesia. Puskesmas merupakan FKTP terbesar yang memperoleh dana kapitasi dengan nilai Rp 8,53 triliun pada tahun 2017. Pemanfaatan dana kapitasi beragam pada setiap Puskesmas. Pembayaran dana kapitasi memiliki tren peningkatan seiring dengan jumlah kepesertaan BPJS Kesehatan yang bertambah menuju universal health coverage. Kajian ini mendalami pemanfaatan dana kapitasi Puskesmas dan capaian SPM Kesehatan. Data penelitian mencakup Puskesams di Kota Cirebon selama periode tahun 2017-2018. Penelitian ini melibatkan variabel SiLPA dana kapitasi dan standar pelayanan minimal kesehatan. Rumusan hipotesis menyatakan terdapat perbedaan capaian standar pelayanan kesehatan minimal bidang kesehatan pada FKTP yang mempunyai SiLPA dana kapitasi rendah dengan puskesmas yang memiliki nilai SiLPA tinggi. Hasil perhitungan uji Lilliefors untuk sampel penelitan menghasilkan nilai L yaitu 0,1725 dengan data berdistribusi normal. Hasil pengujian menunjukkan bahwa tidak terdapat varians capaian standar minimal pelayanan kesehatan pada Puskesmas di Kota Cirebon.